The Cenomanian- Turonian Oceanic Anoxic Event, II. Palaeoceanographic controls on organic-matter production and preservation. - Arthur, M; Schlanger, S; Jenkyns, H (Blackwell Scientific; Geological Society Special Publication, 26, 1987)
The OAE coincided with a maximum sea level highstand. Sea level, which may be responding to some volcano-tectonic event, is the common link and ultimately the driving force for orgC deposition in globally distributed basins under different climatic and ocean circulation regimes. -from Authors